Incumplimiento del pago de pensión de alimentos en niños, niñas y adolescentes del distrito de pueblo nuevo chepén - la libertad, año 2015 - Olivary Villegas, Kiara Jannet Emerita (2016)
This research allowed to acquire knowledge and learn about coherent justifications and practices for faces the problem of fathers and mothers who do not comply with the alimony of their minor children. The report's thesis deals with the causes that generate the non-payment of alimony in boys, girls and adolescents belonging to the Pueblo Nuevo district, Chepén province, Department of La Libertad. The breach of the obligations of food is one of the problems of highest incidence affecting many families of the district and its surroundings; It is said that during subsists family cohabitation, is frequent food are met in kind and in this way the obligor meets its duty, providing everything you need for the sustenance of the petitioner. However, produced rupture of coexistence, usually awareness of this duty begins to crumble. The parent fails to distinguish clearly the fact that even though your marital partner has been terminated, their parental commitment continues, and therefore the mandate of his role as father remains unchanged. As it no longer lives with the children, warns not their needs or deprivations which object makes them not to pay the fee. It is common that the creditor demands asking that who should feed it meets do it, which is usually set a sum of money called alimony; the consequences of these actions together make that children lack decent amenities to survive, such as: food, clothing, education, recreation, housing and health.